Effect of 6-OHDA on hypercapnic ventilatory response in the rat model of Parkinson's disease - Andrzejewski, K; Budzińska, K; Kaczyńska, K (Physiological research, 2019)
Breathing impairments, such as an alteration in breathing pattern, dyspnoea, and sleep apnoea, are common health deficits recognised in Parkinson's disease (PD). The mechanism that underlies these disturbances, however, remains unclear. We investigated the effect of the unilateral damage to the rat nigrostriatal pathway on the central ventilatory response to hypercapnia, evoked by administering 6-hydroxydopamine (6-OHDA) into the right medial forebrain bundle (MFB). The respiratory experiments were carried out in conscious animals in the plethysmography chamber. The ventilatory parameters were studied in normocapnic and hyperoxic hypercapnia before and 14 days after the neurotoxin injection. Lesion with the 6-OHDA produced an increased tidal volume during normoxia. The magnified response of tidal volume and a decrease of breathing frequency to hypercapnia were observed in comparison to the pre-lesion and sham controls. Changes in both respiratory parameters resulted in an increase of minute ventilation of the response to CO(2) by 28% in comparison to the pre-lesion state at 60 s. Our results demonstrate that rats with implemented unilateral PD model presented an altered respiratory pattern most often during a ventilatory response to hypercapnia. Preserved noradrenaline and specific changes in dopamine and serotonin characteristic for this model could be responsible for the pattern of breathing observed during hypercapnia.
Keywords: Medial Forebrain Bundle; Parkinsonian Disorders; Male; Rats; parkinsonské poruchy; Sympatholytics; Hypercapnia; oxidopamin; potkani Wistar; plicní ventilace; Animals; sympatolytika; hyperkapnie; Pulmonary Ventilation; zvířata; mužské pohlaví; Oxidopamine; krysa rodu Rattus; Rats, Wistar; fasciculus telencephali medialis